Peran Baznas Microfinance Desa (BMD) Bojongrangkas Dalam Pemberdayaan Ekonomi Mustahiq - Detasya Salsabiela; Asep Shodiqin; Herman Herman (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2022)
The problem of poverty is a complex problem in Indonesia and is correlated with economic inequality so that there will be a gap between the rich and the poor. This gap is felt in the vulnerable group of micro business actors so that it is difficult to borrow capital from banks and will lead to moneylenders. This research was conducted to reveal the process, program and results of the Bojongrangkas Village Microfinance Baznas (BMD) program in empowering the mustahiq economy. The use of descriptive research used in this study is expected to be able to produce maximum or adequate data through data collection by observation, interviews, documentation. The data analysis technique was carried out by means of data reduction, data presentation, verification and drawing conclusions through a qualitative approach. The results showed that the Bojongrangkas Village Microfinance Baznas (BMD) program in empowering the mustahiq economy in the form of providing capital financing, coaching in the form of training, mentoring to develop businesses and social spiritual aspects through donations. The implementation process goes through several stages starting from the BMFi implementation stage, namely need assessment, HR recruitment and training, program funds, mentoring and monev. That way the perceived output can grow, develop and have business blessings through a culture of giving towards the welfare of the community.